A ATRIBUIÇÃO DO ACENTO NOS ADVÉRBIOS EM –MENTE NO PORTUGUÊS: DISCUSSÃO DE ASPECTOS PROSÓDICOS E RÍTMICOS - Abreu-zorzi, Thais Holanda De (2018)
ABSTRACT This article aims to discuss the prosodic behaviour of adverbs ending in –mente in Archaic Portuguese (AP) and Brazilian Portuguese (BP) from the perspective of Prosodic and Metrical Phonology. In order to describe the prosodic status of such adverbs, especially in AP, 420 cantigas [a genre of poetry], known as Cantigas de Santa Maria (CSM) in praise of Virgin Mary, were chosen, as well as 1251 secular cantigas (510 cantigas de amigo, 431 cantigas de escárnio e maldizer and 310 cantigas de amor). On the other side, a selection of the “Cospus Online do Português” [Online Corpus of the Portuguese Language] database, jointly elaborated by Georgetown University’s researcher Michael Ferreira and Brigham Young University’s Mark Davies, was chosen as the corpus of study of BP. The collection and analysis of –mente adverbs in the corpora made it possible to conclude that these adverbs are, from a prosodic point of view, compounds (having a primary and a secondary stress) both in AP as well as BP, since they can be considered structures formed by independent parts of each other, in which the Stress Placement Rule operates in different domains: in the already inflected bases and in the –mente “suffix”.